Mild hyperbaric hyperoxia improves aerobic capacity and suppresses cardiopulmonary stress during the maximal cycle-ergometer test - Kazufumi Hisamoto; Naoki Okubo; Mako Fujita; Hideki Fukushima; Yoshinori Okizuka; Takashi Yamanaka; Tomoyuki Matsui; Toru Morihara; Tatsuya Hojo; Yoshiyuki Fukuoka; Kenji Takahashi (PLoS ONE, 2025)
Aerobic exercise is more recommended than anaerobic exercise for individuals with cardiopulmonary dysfunction to avoid cardiopulmonary stress. However, their oxygen-carrying capacity is already reduced, making it difficult to exercise enough. Therefore, we aimed to investigate whether mild hyperbaric hyperoxia enhances aerobic capacity and decreases cardiopulmonary stress during exercise with a particular focus on the ventilatory threshold (VT). Nineteen healthy men (age 34.9 ± 10.8 years) performed ramp-loading tests on a cycle-ergometer under the three oxygen conditions: hypobaric hypoxia (HYPO; 0.7 ATA, 14.7% O2), normobaric normoxia (NOR; 1.0 ATA, 21% O2), and mild hyperbaric hyperoxia (HYPER; 1.3 ATA, 35% O2). Cardiopulmonary data were recorded using a gas exchange analyzer. VT was assessed based on minute ventilation (VE) using the V-slope method and the work rate on VT (WVT) was determined. Although the maximal values of VE did not differ among the oxygen conditions, WVT in the HYPER condition was significantly higher compared to others (HYPO; 125 ± 21, NOR; 148 ± 24, HYPER; 168 ± 32 [W], each p < 0.01). Systolic blood pressure and double product on VT in the HYPER condition were significantly reduced compared to others (HYPO; 172 ± 21, 23096 ± 4354, NOR; 173 ± 15, 23377 ± 3109, HYPER; 155 ± 18, 21255 ± 3340 [mmHg, beats·min-1·mmHg], each p < 0.05). Although further clinical research targeting other populations is needed to apply mild hyperbaric hyperoxia in clinical practice, due to its positive effects on WVT and cardiopulmonary stress, the HYPER oxygen condition may potentially be used to enhance aerobic capacity and make individuals with cardiopulmonary dysfunction exercise safely.